2002
DOI: 10.1038/sj.leu.2402636
|View full text |Cite
|
Sign up to set email alerts
|

Minimal residual disease levels in bone marrow and peripheral blood are comparable in children with T cell acute lymphoblastic leukemia (ALL), but not in precursor-B-ALL

Abstract: Sensitive and quantitative detection of minimal residual disease (MRD) in bone marrow (BM) samples of children with acute lymphoblastic leukemia (ALL) is essential for evaluation of early treatment response. In this study, we evaluated whether the traumatic BM samplings can be replaced by peripheral blood (PB) samplings. MRD levels were analyzed in follow-up samples of 62 children with precursor-B-ALL (532 paired BM-PB samples) and 22 children with T-ALL (149 paired BM-PB samples) using real-time quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(77 citation statements)
references
References 27 publications
4
71
2
Order By: Relevance
“…The higher MRD levels in BM are in keeping with the BM origin of AML, comparable with our earlier findings in ALL. 22 Similar findings have been reported for MRD analysis in adult CBFB-MYH11-positive AML patients. 23 In contrast, two adult MRD studies reported comparable MRD levels between BM and PB.…”
Section: Mrd In Paired Bm and Pb Samplessupporting
confidence: 75%
“…The higher MRD levels in BM are in keeping with the BM origin of AML, comparable with our earlier findings in ALL. 22 Similar findings have been reported for MRD analysis in adult CBFB-MYH11-positive AML patients. 23 In contrast, two adult MRD studies reported comparable MRD levels between BM and PB.…”
Section: Mrd In Paired Bm and Pb Samplessupporting
confidence: 75%
“…However, we were neither able to demonstrate a superior role of plasma DNA-based MRD analysis in comparison to conventional MRD analyses relying on DNA from BM or PB cells nor were we able to prove an added clinical value of this method in association with the already-established MRD techniques [34,35].…”
Section: Discussionmentioning
confidence: 72%
“…14,26 One explanation of their findings may be that most of their patients had acute leukemia and that MRD detection in acute leukemia is more sensitively detected in BM than in PB. 30,31 Also, a decreased background expression level of WT1 was seen in the BM of SCT patients as compared to healthy volunteer donors. 14 In some studies, a high initial expression of WT1 in blasts is required in order to assess MRD during follow-up.…”
Section: Discussionmentioning
confidence: 99%